Leave no one behind: why WHO's regional office for Europe should prioritise children and adolescents in their program of work. A position statement from the European academy of paediatrics - Jansen, Danielle; Brenner, Maria; Illy, Károly; Dembiński, Łukasz; del Torso, Stefano; Grossman, Zachi; Valiulis, Arunas; De Guchtenaere, Ann; Mazur, Artur; Da Dalt, Liviana; Størdal, Ketil; Koletzko, Berthold; et al. (Frontiers in Pediatrics, 2023)
Children and adolescents are no longer a priority in the most recent European Programme of Work (EPW) 2020–2025 of the World Health Organization (WHO) Regional Office for Europe. In this position statement we provide arguments for why we think this population should be explicitly addressed in this important and influential document. We firstly emphasize the persistent health problems and inequalities in access to care for children and adolescents that are challenging to solve, and thus require a continuous focus. Secondly, we urge the WHO to prioritize children and adolescents in their EPW due to the new and emerging health problems related to global issues. Finally, we explain why permanent prioritization of children and adolescents is essential for the future of children and of society.